SYMPTOM, THEORY AND POST-TRAUMATIC STRESS MODEL - Felix Lengkong (Universitas Gunadarma, 2007)
The continuous disasters in Indonesia is increasing the possibility of the clinical symptoms on the victims called PTSR and PTSD. Psychosocial approach for this symptoms is important. But, the effect will more curative if clinical approaches is used to handel the PTSD symptoms even though it also depend on the theory and model used by the clinician. That is why this article discusses about PTSD symptoms and its approaches in detail to be able to used by the readers.Key words: clinical symtoms, stress